The NMSU 1 m Telescope at Apache Point Observatory - Jon A. Holtzman; Thomas E. Harrison; Jeffrey L. Coughlin (Advances in Astronomy)
We describe the New Mexico State University (NMSU) 1 m telescope located at the Apache Point Observatory (APO), and in particular, its robotic mode of operation. Some of the issues we have encountered may be of interest to others developing similar facilities. This telescope provides a good example of the possibilities of locating a moderate-sized university robotic research telescope at a major observatory. We find that this mode of operation provides a significant amount of productive science data on a relatively small budget.